HGG-44. DEFECTS OF MISMATCH REPAIR PROTEINS IN PEDIATRIC HIGH GRADE GLIOMAS. (4th December 2020) - Haberler, Christine; Muller, Philippe; Müllauer, Leonhard; Peyrl, Andreas; Czech, Thomas; Wimmer, Katharina; Slavc, Irene
Abstract: Hetero- and homozygous germline mutations of the mismatch repair genes MLH1, PMS2, MSH2 and MSH6 cause Lynch and constitutional mismatch repair (CMMRD) cancer predisposition syndrome, respectively. Affected CMMRD individuals are at risk to develop a variety of neoplasms including CNS tumors, particularly high grade gliomas (HGG), during childhood. Currently, few data exist on the prevalence of CMMRD in children with pediatric HGG. We screened a consecutive series of 79 supratentorial HGGs. Tumor tissue was available in 42 patients, 5 were reclassified as non-HGGs. Immunohistochemistry with antibodies against MLH1, PMS2, MSH2 and MSH6 was performed in 37 tumors. Four patients (3 families) with known CMMRD were included. The evaluation of the slides was performed blinded to the CMMRD status. All four patients with known CMMRD (3 patients with PMS2, one with MSH6 mutation) were identified, showing loss of PMS2 and MSH2/MSH6, respectively. Additionally, we identified 6 patients with loss of MSH2/MSH6 staining in tumor cells, but retained staining in preexisting cells, indicating a pattern like in Lynch syndrome. NGS sequencing of these tumor tissues revealed in 2 patients MSH2 mutations and in one patient a hypermutator phenotype with MSH2 and MSH6 mutations. In 3/6 patients no mutations in the MMR genes were detectable. In summary, we found a low prevalence of CMMRD among HGGs, but identified also 2 patients with probable Lynch syndrome. Immunhistochemistry is an effective tool to screen for patients with MMR defects and should be performed in HGGs to optimize treatment and offer affected families genetic counseling.